KARAKTERISTIK HABITAT DAN TINGKAT KEMATANGAN GONAD KEPITING KELAPA (Birgus latro) DI PULAU UTA, PROPINSI MALUKU UTARA - Supyan Supyan; Sulistiono Sulistiono; Etty Riani (Jurusan Perikanan dan Kelautan, 2013)
Coconut crab (Birgus latro) is one of the species of crustaceans that economically valuable. The research aimed to investigate habitat characteristics and gonad maturity of Coconut crabs (Birgus latro) in Uta Island, North Mollucas. Sampling was conducted through cruising survey from May to September 2012, while parameters examined to the habitat characteristics and reproductive aspects were physical-chemical, gonad maturity, and vegetation existence. Habitat characteristics were assessed using Cluster Analysis. Result showed that length and weight relationship of male crabs wasW= 1.93 (CP + r), while the female was 1.17W= 1.97 (CP + r) 0.97. During the observation, it showed that mature gonad occurred in all catching time indicating that it didn’t occur simultaneously on the broodstock. The smallest crabs were found 65.44 mm in length (CP + r). There was no significant different of sex ratio between males and females (1:1). Disparity of habitat characteristics in each station doesn’t affect to the catch, both the quantity and level of gonad maturity. Habitat conditions at all stations strongly supported their activities to live sustainably.